Importance of Globalization Process and Its Impacts on Turkish Economy - Mirac, Altuntaş (Wydawnictwo Uniwersytetu Rzeszowskiego, 2012)
Globalization is the most important tool of the economy planning on international scale in a manner consistent and occurring in the integrated world economy. Factors effecting economy also effects globalization. In this context, it is difficult to give a single definition of globalization. The simplest form of globalization is gradual increase of communication and interaction between the communities living on the Earth, within the framework of interdependence. Globalization is not a new concept. Especially after World War II, more than one country tried to be the best not only in term of the economic also in political area. Therefore, many undeveloped and developing countries became a potential market for those powerful countries. In this study, the importance of globalization process and its effects on Turkey’s economy are investigated. Turkey is greatly influenced by the globalization process. Turkey’s strategic location is one of the most important reasons for this influence. Turkey embraces two continents, one arm reaching out to Asia, the other to Europe. Turkey hosts many civilizations, which has both positive and negative impacts on the country’s economy. In 1980, Turkey has undergone a fundamental structural change to ensure compliance with the world economy and economic globalization. Protectionist economic structure has become freer, export was more encouraged than import, foreign trade, currency, interest, and capital accounts were liberalized. In today’s economy, globalization is gaining momentum with trade volume increasing.

Globalizacja stanowi najważniejszy czynnik zmian gospodarczych w skali międzynarodowej, oddziałujący w zintegrowanej gospodarce światowej. Inne czynniki determinujące sytuację gospodarczą również pozostają pod wpływem globalizacji. W tym kontekście trudno jednoznacznie zdefiniować pojęcie globalizacji. W najprostszy sposób można ją określić jako stopniowy wzrost komunikacji i interakcji pomiędzy społeczeństwami na całym świecie, w ramach wzajemnych współzależności. Globalizacja nie jest koncepcją nową. W szczególności po II wojnie światowej wiele państw dążyło do przejęcia dominacji zarówno w sferze gospodarczej, jak i politycznej. Stąd też wiele słabo rozwiniętych i rozwijających się krajów stało się potencjalnym rynkiem dla najsilniejszych gospodarek. W opracowaniu analizom poddano znaczenie procesu globalizacji i jego oddziaływanie na gospodarkę Turcji. Turcja pozostaje pod znacznym wpływem procesów globalizacji. Jedną z najistotniejszych przyczyn tego oddziaływania jest strategiczna lokalizacja Turcji. Turcja usytuowana jest na dwóch kontynentach: azjatyckim i europejskim. Turcję charakteryzuje różnorodność cywilizacyjna, co ma zarówno pozytywny, jak i negatywny wpływ na gospodarkę turecką. W 1980 r. Turcja doświadczyła fundamentalnych zmian strukturalnych, które zapewniły jej spójność z gospodarką światową i poddały ją wpływom globalizacji gospodarczej. Protekcyjna struktura gospodarcza została urynkowiona, eksport wzrósł w większym stopniu niż import, waluta, stopy procentowe i rachunki kapitałowe zostały zliberalizowane. Współcześnie globalizacja skutkuje wzrostem wolumenu handlu.